Peru : Technical Assistance Report-Tax Regime for Small Taxpayers and Special Economic Zones. (IMF Staff Country Reports; Country Report ;, 2022)
The topics discussed in this report are tax regimes for small taxpayers (Chapter II) and the tax treatment of special economic zones (Chapter III). Although these aspects of the tax system have little direct effect on public finances, they affect many people and how those people make decisions or impact the positioning of certain regions relative to the rest of the country. Both are of social and political scope that is disproportionate to their magnitude of tax revenue collection, which is why their design must remain focused in its most strategic sense.